Effects of processing and fat removal on the value of cottonseed in diets for lactating dairy cows - M. J. Meyer; Evan C. Titgemeyer; Michael V. Scheffel; A. F. Park (Kansas Agricultural Experiment Station Research Reports, 1999)
Eighteen Holstein cows were used in six simultaneous 3x3 Latin squares to determine the value of extruded-expelled cottonseed meal with lint as a replacement for whole cottonseed in diets for lactating dairy cows. Diets were: 1) WCS=whole cottonseed; 2) EC+T=extruded-expelled cottonseed meal with tallow; and 3) EC=extruded-expelled cottonseed meal. Diets were formulated to contain 17.5% CP and 40% RUP. Tallow or shelled corn was used to balance energy across diets. No differences were observed in dry matter intake, milk production, or feed efficiency among diets. Cows fed EC produced milk with a slightly higher protein percentage. Feed costs per cwt of milk were $4.17, $4.19, and $4.11 for WCS, EC+T, and EC, respectively. Extruded-expelled cottonseed meal with lint can replace whole cottonseed in diets for lactating dairy cows, if the diet is balanced for energy with either corn grain or tallow.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Extruded cottonseed; Tallow; Cottonseed; Lactating cows